The Effect of the Inclusion of Uncertainty on the Optimal Allocation of Resources to Climate Change Mitigation and Adaptation Programmes. Issue 1 (March 2014) - Maybee, Bryan M.; Packey, Daniel J.
<x xml:space="preserve">Abstract</x> How to deal with our changing climate is one of the most controversial topics facing modern society. The two most prevalent choices are to mitigate the effects through global programmes, or adapt to the changes at the local level. While both have positive and negative traits, the reality is that a combination of the two strategies is required. This is the second study in a series investigating the mitigation–adaptation balance from an economic perspective. Using an expected value approach, this study discusses the theoretical sources and impact of uncertainty associated with implementing a mitigation or adaptation programme on the strategic optimisation.